Pergeseran Bahasa Dayak Pada Masyarakat Loksado Kabupaten Hulu Sungai Selatan Provinsi Kalimantan Selatan - Ida Komalasari; Kamal Hasuna; Heppy Lismayanti (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
At this time Indonesia has occurred the shift in the use of local languages among the speakers. This shift is feared to be able to make the younger generation as the successor to the nation is slowly leaving and did not know the language and the local wisdom of his forefathers. Various factors certainly have affected the occurrence of such a shift. This is particularly of concern for experts, observers, activists, researchers, and local languages, including the press, as well as employees of the Government. Various efforts need to be made by all parties in order to pemertahanan the language of the area. The issues facing the BD is currently the position and its functions no longer correspond to the position and the function of which was given to him. Local languages are no longer made as a boast of identity, as well as their functions are no longer made as the main communication language in family life and community supporters. The problem of language extinctions is starting to attract the attention of many circles, not just from among linguists, but also by the general public. Formulation of the problem: (1) how did the Dayak language shift conditions on the Dayak Society Hill in Hulu Sungai Selatan Regency Loksado?, (2) what are the factors that affect the shifting language of Dayak Dayak Society Hill in Hulu Regency Loksado South River. In this study used a qualitative approach. This research is located in district Loksado District South of the River in South Kalimantan Province. This research data is data Dayak language shift conditions in various domains. First, in the form of speech is spoken by the Dayak communities when communicating, namely in the form of words, sentences, and phrases to know the condition of the Dayak Language usage in a variety of domains. This data was obtained by recording the event said at a time when the situation in the family, neighbors, education, religion, transactions, and Government.